SISTEM AGRIBISNIS DAN KEMITRAAN USAHA PENGGEMUKAN SAPI POTONG DI KOPERASI GUNUNG MADU - Rani Satiti; Dyah Aring Hepiana Lestari; Ani Suryani (Lampung University, 2017)
The purpose of this research are to: study realization of treaty in beef cattle fattening, study the procurement process of raw materials to meet the six precise (on time, exact place, quality, quantity, type, and price), analyze profits of beef cattle fattening, study the marketing channels of beef cattle fattening, study the supporting services’s role to beef cattle fattening. This research is a case study at Gunung Madu Cooperation in Gunung Batin Baru Village, Terusan Nunyai Sub District, Central Lampung Regency that is choosen on purpose with consideration that Gunung Madu Cooperation partnershiped with PT Indo Prima Beef about one year. The data collected in December 2016 and analyzed by a qualitative descriptive analysis and quantitative descriptive analysis. The results of research showed that the realization of treaty between Gunung Madu Cooperation and PT Indo Prima Beef have a good realization until three period. The raw materials procurement of beef cattle fattening met the component of six precise. Beef cattle fattening in Gunung Madu Cooperation was viable because its R/C ratio value was greater than one in one to three periods. The marketing channels of beef cattle fattening were precised because involving the intitutional agency. All supporting services were utilized by beef cattle fattening Gunung Madu Cooperation namely extension services, transportations, government policies, information and communication technnology give positive role.Key words: agribusiness system, beef cattle, cooperation, partnership